Diet and Culture Among Chinese Patients Undergoing Hemodialysis: A Qualitative Study - Song, Yan; Wang, Jing; Liu, Huan; Chen, Xiaolan; Zhan, Minqi (Frontiers in Nutrition, 2022)
A growing body of research showed that diet management, such as promoting protein and vitamin intake and food restriction play a crucial role in extending time to morbidity and mortality in patients undergoing hemodialysis. However, the current dietary recommendations in nutrition guidelines lack examination of cultural factors. The study aimed to understand the diet influenced by culture in Chinese patients undergoing hemodialysis. Semi-structured interviews were conducted for 23 patients, aged 23–75 years, undergoing hemodialysis in a local tertiary hospital. Interview questions mainly focused on patients’ real experience about diet, and their perceptions and attitudes towards diet. Each interview was digitally recorded, and conventional content analysis was used to attain information. The majority of patients reserved Chinese traditional dietary habits about salt and calcium intake. Although Chinese herbal medicine was not consumed, dietary therapy including brown sugar and dates was included in the participants’ diet. Eggs, broth, and seafood were three prominent preferences and taboos profoundly impacted by culture. Additionally, Chinese social culture influenced patients’ dietary behavior of eating at home and knowledge attainment. Diet in Chinese patients undergoing hemodialysis was still strongly influenced by culture. Culturally sensitive interventions regarding the improvement of diet intake are urgently needed.